A META-ANALYSIS OF THE FILTER BUBBLES ON SOCIAL MEDIA: RESEARCH NOVELTY AND ITS IMPLICATIONS FOR UNDERSTANDING THE CHARACTER OF PANCASILA - Achdyat, Achdyat; Budimansyah, Dasim; Nurdin, Encep Syarief; Hidayat, Mupid (International Journal of Education, 2025)
The phenomenon of filter bubbles on social media disrupts a comprehensive understanding of Pancasila and triggers opinion polarization that threatens national unity in Indonesia. This study aims to examine the development of research related to the filter bubble phenomenon by utilizing a meta-analysis literature study method. The data sources used are Google Scholar, with the application Publish or Perish to identify research trends. Further, novelty analysis of the research was conducted using the VOSviewer application. The search was conducted on international journal publications indexed by Google Scholar using the keywords "filter bubble, social media" from 2013 to 2023, and a total of 985 articles were found. Findings indicate that publications related to this topic have seen a relatively high increase from 2013 to 2023, suggesting a potential trend for increased research interest in the coming years. From the data obtained, results indicate that there are several interesting topics as research novelties, including filter bubbles on social media and their implications for the distortion of understanding Pancasila's character. The implications of the Filter Bubble phenomenon on the understanding of Pancasila's character create significant challenges in efforts to build strong national awareness and identity in Indonesia. Filter bubbles narrow access to information, potentially reducing a comprehensive understanding of Pancasila and triggering opinion polarization that threatens national unity. Further research is needed to examine the mechanisms of filter bubbles and mitigation strategies to strengthen understanding of Pancasila and build inclusive national solidarity. Additionally, this article is also important as a source of data for the development of research on the topic of filter bubbles.